A body in Boston - Fletcher, Jessica; Moran, Terrie Farley (Fletcher, Jessica. Murder, she wrote, 2025)
"Jessica Fletcher has dinner with her old pal Harry McGraw and gets pulled into a puzzling murder case. Invited to deliver a lecture at the Boston Public Library, Jessica Fletcher excitedly makes plans to see local friends. Naturally that includes dinner at Gilhooley's with PI Harry McGraw. Harry excitedly talks about his latest client, the CEO of Cure All Pharmaceuticals, who's received anonymous blackmail demands and wants Harry to identify the culprit. Cookie, Gilhooley's longtime bartender, also has something he wants to tell Jessica: Hae asked Harry to investigate his daughter Aileen's boyfriend, whom Cookie thinks is too slick by half, but now Harry is too wrapped up in this new case. While Jessica wonders how best to approach Aileen, the young woman stumbles into Gilhooley's covered in blood. She just discovered her boyfriend's corpse - and quickly becomes the chief suspect in his murder!"--